Die Religionen in vorgeschichtlicher Zeit. (Die Religionen der Menschheit Bd. 2), Ina Wunn : book review - Riekert, S. J. P. K. (Old Testament essays, 2006)
Extracted from text ... Wunn, Ina 2005. Die Religionen in vorgeschichtlicher Zeit. (Die Religionen der Menschheit Bd. 2). Stuttgart: Kohlhammer. x + 496 pages. Cloth with dust cover. Euro 89.00 ISBN 3-17-016726-X This work by Ina Wunn, the second volume, is the latest addition to a renowned series. The review starts from the perspective of scholarship in the field of Old Testament and Christian Studies and related fields. Many Old Testament scholars would have used Morenz's gyptische Religion, Volume 8 of the series; Die Religionen Altsyriens, Altarabiens und der Mander by Gese and others, published as Volume 10, 2, and Ringgren's Israelitische Religion ..